2014
DOI: 10.1021/jp5066067
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Bare UO22+and NUO+by Fragmentation of Gas-Phase Uranyl–Acetonitrile Complexes

Abstract: In a prior study [Van Stipdonk; et al. J. Phys. Chem. A 2006, 110, 959-970], electrospray ionization (ESI) was used to generate doubly charged complex ions composed of the uranyl ion and acetonitrile (acn) ligands. The complexes, general formula [UO2(acn)n](2+), n = 0-5, were isolated in an 3-D quadrupole ion-trap mass spectrometer to probe intrinsic reactions with H2O. Two general reaction pathways were observed: (a) the direct addition of one or more H2O ligands to the doubly charged complexes and (b) charge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
37
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 79 publications
3
37
1
Order By: Relevance
“…However, in a recent investigation of the fragmentation behavior of UO 2 2+ complexes containing acn [27], we showed that the amount of adventitious H 2 O in the LIT is significantly lower than in the 3-D ion trap employed in our previous studies. CID was used to drive complete acn ligand elimination to generate UO 2 2+ , and this was the first reported generation of the bare di-cation by multiple-stage CID.…”
Section: +contrasting
confidence: 57%
“…However, in a recent investigation of the fragmentation behavior of UO 2 2+ complexes containing acn [27], we showed that the amount of adventitious H 2 O in the LIT is significantly lower than in the 3-D ion trap employed in our previous studies. CID was used to drive complete acn ligand elimination to generate UO 2 2+ , and this was the first reported generation of the bare di-cation by multiple-stage CID.…”
Section: +contrasting
confidence: 57%
“…Formation of [MCH 3 ] + (M = metal) product ions by heterolytic C–C bond cleavage has been reported by Wu et al following CID of transition‐metal complexes of composition [M 2 + (acetone) 2 ] 2+ . Heterolytic cleavage to liberate CH 3 has also been observed following CID of metal–acetonitrile complexes, including those that contain UO 2 2 + . However, in this case the CN − fragment remains coordinated to the metal ion.…”
Section: Resultsmentioning
confidence: 86%
“…Recently, we began to revisit the CID of uranyl complexes using a linear quadrupole ion trap (LIT). In an investigation of the fragmentation behavior of uranyl complexes containing acetonitrile (acn), we showed that the amount of adventitious H 2 O in the LIT is significantly lower than in the 3‐D ion trap employed in our previous studies. The low partial pressure of the H 2 O allowed the fragmentation chemistry of the species to be studied more completely.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…[11] The gentle ionization process involved in this technique is suitable for transferring the species from solution to the gas phase with the retention of stoichiometry. In recent years, the formation of uranyl complexes has been studied in great detail using ESI-MS. [12][13][14][15][16][17] For example, direct infusion of solution into the mass spectrometer has helped to ascertain the stoichiometry and stability constants of uranyl complexes with 1hydroxyethane-1,1'-diphosphonic acid (HEDP). The mass spectrometric data were found to be in close agreement with those derived from conventional techniques such as potentiometry and spectroscopy.…”
mentioning
confidence: 99%